UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH PADA PERMAINAN BOLA VOLI DENGAN MENGGUNAKAN METODE COOPERATIVE LEARNING TYPE GROUP INVESTIGATION PADA SISWA KELAS VIII SMP NEGERI 1 AMBALAWI KABUPATEN BIMA - Jurahman, Jurahman; Wardani, Intan Kusuma (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Based on observations of researchers from Class VIII Middle School 1 Ambalawi Bima District, there are still many students who are less able to do lower passing. One of the factors that causes a lack of success in the results of lower passing learning is the lack of motivation of students in learning to pass under, because the method used is not in accordance with the characteristics of students. The formulation of the problem in this study is "How is the effort to improve the results of lower passing learning on volleyball games by using the Cooperative learning type group investigation method in Class VIII Students of Middle School 01 Ambalawi, Bima Regency ?. The purpose of this study was to improve the results of lower passing learning on volleyball games by using the method of cooperative learning type group investigation in class VIII SMP Negeri 1 Ambalawi Bima District. The research design used was classroom action research. The population in this study, namely Class VIII Students of SMP Negeri 1 Ambalawi Bima District, while the sample used was students of class VIII / A Middle School 1 Ambalawi which amounted to 30 students. The results of this study are that there is an increase in student learning achievement in the under-passing of volleyball in the first cycle and second cycle which is significant. This is evidenced from the results of calculations with an average value in the first cycle of 68.99 and the second cycle is 72.58. Which means that there is an increase in student achievement from cycle to cycle. The results of the second cycle show that the completeness of student learning outcomes in the under-passing volleyball game has reached KKM (KKM = 70). In other words, classical completeness has reached the target of 80%.